2012
DOI: 10.5120/5629-7977
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Feature based Natural Scene Classification using Neural Network

Abstract: In this paper a classification for natural images is proposed using hybrid features. The objective of this paper is to develop an image content based classifier, which can perform identity check of a natural image. Here we have extracted wavelet and color features from a captured natural image to classify out of three groups. The developed technique is able to classify translation and rotation invariant matching among natural images using feed forward back propagation neural network. The database contains seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…It has been shown that the highest classification rate was obtained using the multi-scale wavelet-based features. A correct classification rate of 97% has been obtained which is comparable to similar neural networks classifiers used in [1], [2], [19]. The results are encouraging and promising.…”
Section: Sensitivity= True Positives/(true Positive + False Negative)supporting
confidence: 67%
“…It has been shown that the highest classification rate was obtained using the multi-scale wavelet-based features. A correct classification rate of 97% has been obtained which is comparable to similar neural networks classifiers used in [1], [2], [19]. The results are encouraging and promising.…”
Section: Sensitivity= True Positives/(true Positive + False Negative)supporting
confidence: 67%